SPECIAL PHYSICAL TRAINING IN FRAME RANNING SPORT DISCIPLINES OF PERSONS WITH LESIONS OF THE MUSCULOSKELETAL SYSTEM - Voroshin, I.N.; Dmitriev, I.V.; Maslennikov, A.V.; Mironov, A.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the main directions and content of special physical training in the disciplines of frame-running sports of people with musculoskeletal disorders. Methods and structure of the study. At the first stage, the leading athletes of the world, specializing in the studied disciplines, took part in the ascertaining experiment. This experiment was carried out to identify the main muscle groups involved in a competitive exercise, and also identified special physical qualities, the development of which is a paramount task in the physical preparation of a runner on a frame running. At the second stage of the ascertaining experiment, the leading athletes of Russia, specializing in the disciplines under study, took part in order to determine pedagogical tests that can comprehensively assess the level of development of special physical qualities of an athlete specializing in frame running disciplines. Results and conclusions. It has been established that at a competitive distance of 100 m in frame running disciplines, special physical qualities are speed-strength qualities, explosive strength, speed endurance, strength endurance. The main muscle groups that need to be developed during special physical training are the hip flexors, lower leg flexors, knee extensors, and hip extensors. As a result of the studies carried out in the course of the ascertaining experiment, a set of pedagogical tests was determined, with the systemic use of which it is possible to identify the dynamics of the special physical fitness of athletes in the studied disciplines.